Phase I Trial of Fourth-Generation Anti-CD19 Chimeric Antigen Receptor T Cells Against Relapsed or Refractory B Cell Non-Hodgkin Lymphomas - Zhou, Xuan; Tu, Sanfang; Wang, Chunsheng; Huang, Rui; Deng, Lan; Song, Chaoyang; Yue, Chunyan; He, Yanjie; Yang, Jilong; Liang, Zhao; Wu, Anqin; Li, Meifang; et al. (Frontiers in Immunology, 2020)
Background: The administration of second- or third-generation anti-CD19 chimeric antigen receptor (CAR) T cells has remarkably improved the survival of patients with relapsed or refractory B cell malignancies. However, there are limited clinical results from fourth-generation CAR-T cell therapy, and the factors affecting response rate and survival have not been fully determined. Methods: Lymphoma patients with progression or relapse after intensive treatments, including hematopoietic stem cell transplantation, and life expectancy >2 months were enrolled in the study. Peripheral lymphocytes were collected through apheresis, and magnetically selected T cells were lentivirally transduced with a 4th-generation CAR featuring an anti-CD19 CAR and the iCasp9 suicide switch (4SCAR19). The patients received 4SCAR19 T cell infusion after approximately seven days of expansion and a conditioning regimen comprising cyclophosphamide/fludarabine. The efficacy, safety and risk factors were evaluated. Results: A total of 21 patients with relapsed/refractory B cell non-Hodgkin lymphoma were enrolled and received 4SCAR19 T cell infusions at a median dose of 8.9×105 CAR-T cells/kg. The overall response rate was 67% (95% confidence interval [CI], 43 to 85), with 43% of patients achieving a complete response and 24% having a partial response. The overall and complete response rates were 58% and 33% in the DLBCL group and 78% and 56% in the non-DLBCL group, respectively. The median overall survival was 23.8 months (95% CI, not reached), with a median follow-up of 13.7 months. Factors affecting overall survival were International Prognostic Index (IPI), disease type, and remission status after CAR-T cell treatment. The most common adverse events of grade 3 or 4 during treatment were neutropenia (76%), leukopenia (71%), and thrombocytopenia (29%). The incidence of cytokine release syndrome (CRS) was 14%, and all cases were grade 1. One patient developed grade 3 neurotoxicity. No deaths were attributed to infusion of 4SCAR19 T cells, CRS, or neurotoxicity. Conclusions: In this study, patients with relapsed or refractory B cell non-Hodgkin's lymphoma who received 4SCAR19 T cell therapy had durable responses and few of adverse events. The IPI model is suitable for evaluating the prognosis of patients receiving CAR-T cell therapy. Trial registration: Chinese Clinical Trial Registry (http://www.chictr.org.cn): ChiCTR-OOC-16007779.